Pericardial Fat Relates to Disturbances of Glucose Metabolism in Women with the Polycystic Ovary Syndrome, but Not in Healthy Control Subjects. (7th August 2018) - Leutner, Michael; Göbl, Christian; Wolf, Peter; Maruszczak, Katharina; Bozkurt, Latife; Steinbrecher, Helmut; Just-Kukurova, Ivica; Ott, Johannes; Egarter, Christian; Trattnig, Siegfried; Kautzky-Willer, Alexandra
Abstract : Objective . The objective of the present study is to investigate the relationship of cardiac fat depots with disturbances of the carbohydrate metabolism in women with PCOS. Methods . An oral glucose tolerance test (OGTT) was realized, and metabolic parameters were collected in 48 women with PCOS and in 20 controls. Intramyocardial fat (MYCL) and pericardial fat (PERI) were measured using 1 H-magnetic resonance spectroscopy and imaging. Results . Only in PCOS women, PERI was positively and independently related to parameters of glucose metabolism (HbA1c:p = 0.001, fasting plasma glucose:p < 0.001, stimulated glucose at 30 and 60 minutes in the OGTT). Thus, the disposition index, insulin sensitivity, and adiponectin also declined with the increase of PERI in women with PCOS; however, these results were not independent of BMI and age. In addition, PERI was positively related to atherogenic lipid profiles, BMI, waist circumference, CRP, and liver fat in women with PCOS. A negative relation of PERI with triglycerides and a positive relation with BMI and waist circumference could be observed in the controls. No relationship of MYCL with diabetes-specific parameters could be found in the study population. Conclusion . PERI is related to metabolic disturbances in women with PCOS, but not in metabolically healthy lean subjects. This clinical trial was registered at ClinicalTrials.gov and has the registration numberNCT03204461 .